Accounting for meaning: On §22 of David Foster Wallace's The Pale King. (June 2015) - Michaelson, Christopher
Abstract: The Pale King (2011) is David Foster Wallace's iconic portrait and parody of a modern workplace that is also, not accidentally, an accounting institution – namely, the United States Internal Revenue Service. Many reviewers summarize its topic as boredom – of work in general, and tax accounting in particular. However, its longest section is a nearly one hundred-page, first-person narrative of how one Chris Fogle found his "calling" in accounting, including an accidental encounter with a professor who deemed it to be nothing less than "heroic." Examined through the lens of ethical criticism, §22 of The Pale King is an important text for examining moral questions about what makes work meaningful and whether we have obligations to perform it ourselves and provide it to others. Through the lens of literary critical theory, it can also be read as a commentary on the meaningfulness (or meaninglessness) of accounting and what its methods imply about what has meaning and value in work and life.